2015
DOI: 10.1002/btpr.2039
|View full text |Cite
|
Sign up to set email alerts
|

Combined hypoxia and sodium nitrite pretreatment for cardiomyocyte protection in vitro

Abstract: Methods that increase cardiomyocyte survival upon exposure to ischemia, hypoxia and reoxygenation injuries are required to improve the efficacy of cardiac cell therapy and enhance the viability and function of engineered tissues. We investigated the effect of combined hypoxia/NaNO2 pretreatment on rat neonatal cardiomyocyte (CM), cardiac fibroblast, and human embryonic stem cell-derived CM (hESC-CM) survival upon exposure to hypoxia/reoxygenation (H/R) injury in vitro. Cells were pretreated with and without hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Hsieh et al found that the simulation of IRI in hESC-CMs caused an increase in the qPCR ratio of anti-apopototic BCL-2 to the apoptotic BAX gene following a pretreatment with sodium nitrite [62]. Paloczi et al demonstrated the cardioprotective effect of exogenous nitric oxide supplementation in simulated IRI experiments on hESC-CMs derived from embryoid bodies (EB) [45].…”
Section: In Vitro Models Of Irimentioning
confidence: 99%
“…Hsieh et al found that the simulation of IRI in hESC-CMs caused an increase in the qPCR ratio of anti-apopototic BCL-2 to the apoptotic BAX gene following a pretreatment with sodium nitrite [62]. Paloczi et al demonstrated the cardioprotective effect of exogenous nitric oxide supplementation in simulated IRI experiments on hESC-CMs derived from embryoid bodies (EB) [45].…”
Section: In Vitro Models Of Irimentioning
confidence: 99%
“…Indeed, several studies describe little or no response to I/R-mimetic conditions in unprimed hPSC-CMs, although showing minimal but relatively significant cardioprotection by the individual molecules of interest (Hsieh et al, 2015;Wei et al, 2017;Mo et al, 2019). Our own experiments with oxygen/glucose deprivation in microfluidic devices show clearly divergent responses of postnatal murine cardiomyocytes and unprimed hPSC-CMs characterized by abnormal intracellular glycogen stores (Martewicz et al, 2018).…”
Section: Ischemia/reperfusion Injury Modelingmentioning
confidence: 71%
“…Similar results were presented by our group on mouse embryonic stem cell-derived cardiomyocytes, where NO had concentration-dependent direct cytoprotective action and soluble guanylate cyclase, PKG, and KATP channels play a role in the downstream pathway of SNAP-induced cytoprotection [ 15 ]. Hsieh et al showed recently that short pretreatment with NO donor (NaNO 2 ) combined with hypoxia protects neonatal cardiac myocyte but not cardiac fibroblast from hypoxic injury, and apoptosis decreased in human ES-derived cardiac myocytes [ 34 ]. These results further suggest that NO donors may protect stem cells implanted into ischemic areas of the myocardium.…”
Section: Discussionmentioning
confidence: 99%